Peran Sekolah Indonesia Davao Dalam Membangun Wawasan Budaya Indonesia Di Lingkungan Sekolah - Cucu Widaty; Yuli Apriati; Muhammad Barto Maulana Irsyad Baso; Cindy Wulandari Sutrisno; Muhammad Faqih; Sendi Pustika Sari; Rizky Irvandi (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2026)
This study aims to analyze the role of Sekolah Indonesia Davao (SID) in building Indonesian cultural insight among students in a multicultural environment. The study used a qualitative descriptive approach through interviews with teachers and school stakeholders. The findings show that Indonesian cultural values are integrated through classroom learning, school habituation, extracurricular activities, and collaboration with the Indonesian Consulate General in Davao. Teachers play an important role in embedding nationalism, mutual cooperation, politeness, tolerance, and the use of the Indonesian language in daily learning activities. Cultural reinforcement is carried out through contextual learning, arts performances, national commemorations, and cultural diplomacy programs. However, challenges remain, including strong local cultural influences, limited learning resources, and students’ low use of Indonesian language outside school. The support of teachers, school leaders, parents, communities, and the Indonesian Consulate significantly strengthens the implementation of cultural education at SID. This study concludes that SID has a strategic role as an educational institution and cultural diplomacy center in strengthening Indonesian cultural identity among students abroad.